2021
DOI: 10.1186/s12875-021-01489-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of family caregivers of patients with COVID-19

Abstract: Background Family caregivers of patients with COVID-19 face many challenges that affect their physical and mental health. Aim The aim of the present study was to explore experiences of family caregivers of patients with COVID-19. Methods This phenomenological study was performed based on 13 family caregivers who had experience in home caring for patients with COVID-19. Data were collected through purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
52
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 36 publications
12
52
3
8
Order By: Relevance
“…Additionally, family members need proper information, e.g. about the trajectory of mental health symptoms [ 12 ]. The present study provides clinicians with this information, enabling them to better inform COVID-19 survivors and family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, family members need proper information, e.g. about the trajectory of mental health symptoms [ 12 ]. The present study provides clinicians with this information, enabling them to better inform COVID-19 survivors and family members.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, family members had less contact with clinicians who were taking care for their loved ones, while well-perceived communication and emotional support from clinicians are proven to be important to mitigate PICS-F in non-COVID-19 ICU survivors [ 7 ]. Furthermore, the lack of information about prognosis and long-term outcomes was often reported as a stressor by family members of COVID-19 ICU survivors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the COVID-19 pandemic, various studies have been reported in the literature measuring the anxiety and depression frequency of COVID-19 patients and/or their relatives or referring to their experiences [ 7 , 8 , 9 , 10 ]. In addition, in a previous study, we reported by measuring the anxiety and depression levels of the relatives of patients who were followed up in the intensive care unit with the suspicion of COVID-19 during the pandemic [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research fndings have well established the relationship between social support and increasing the quality of caregiving. In the presence of social support, patient care becomes a valuable experience for families and health care providersy caregivers in addition to meeting patient need [14,15]. The program of "each home as a health post" in Iran, had caused families to participate in following the instructions.…”
Section: Discussionmentioning
confidence: 99%
“…With the onset of the outbreak of COVID-19, the lack of medical facilities, equipment, and staf has affected health care systems and community members around the world. The result of some studies showed that lack of access to medical equipment for caregivers made caring for COVID-19 patients a challenge In the study of Rafati et al, resource constraints were considered as the most important challenge in preventing of COVID-19 [15]. In such pandemic emergencies, health policymakers and other community members must provide a comprehensive system of support for them.…”
Section: Discussionmentioning
confidence: 99%